Development of Learning Materials through CTL with Karo Culture Context to Improve Students’ Problem Solving Ability - Atania Christianti Ginting; Pargaulan Siagian; Edy Surya (Study Program of Mathematics Education of Unimed Postgraduate Program, 2023)
The study aims to: 1) develop valid, practical, and effective quality learning materials for class VII SMP Berastagi 1 Program that focuses on the contextual teaching and learning model with the Karo cultural context (CTL-KCC); and 2) examine the enhancement of students' math problem-solving abilities as a side effect of using CTL-KCC learning materials. This research is development research using a 4-D development model consisting of four stages: define, design, develop, and disseminate. This research yielded learning materials such as learning implementation plans, student books, student worksheets, and mathematical problem-solving ability tests.The following conclusions were uncovered as a result of the research:1) In regards to their respective criteria, CTL-KCC learning materials had also met the valid, practical, and effective criteria.2) The N-gain value during the first trial of 0.30 for the